Analysis of Elasticity and Buoyancy and Projection of Tax in Nepal - Dangal, Dil Nath (Tribhuvan University Journal, 2018)
This study has been designed to calculate elasticity and buoyancy and projection of various taxes in Nepal from 2018 to 2020. This study is based on secondary data published by the government of Nepal covering a period between the fiscal year 2000 to 2016. The various sources of revenue as a proportion of the Gross Domestic Product (GDP) have been analyzed during this period. This study particularly deals with the analysis of elasticity and buoyancy of tax and nontax revenue. The projection of tax revenue since 2018 to 2020 has also been forecasted. The findings reveals that the overall tax system of Nepal seemed to be inelastic during study period, and direct taxes appeared smaller elasticity’s than indirect taxes and those buoyancy coefficients of major taxes became much higher than their respective elasticities.